(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2002)
The small Faella collection of fossil vertebrates, from the Upper Valdarno (UV) continental sediments, was first assembled in the Natural history museum of Firenze over two centuries ago, reaching 13 specimens for 7 represented species, until in 1967 new finds were retrieved from the Cava Pratigliolmi clay pit. The latter were mainly collected in the lower stratigraphic levels, reaching 29 specimens for 10 species, while the position of the ancient specimens, which are among the most representative ones of the Late Villafranchian mammal age, was tentatively determined from catalogue informations. The magnetic stratigraphy of the clay pit sequence at Faella, and additional controls on their database led to assign them an age of 1775 + - 0.05° Ma. Each recent specimen was assigned a numerical age comprised in the time-span measured in the composite Faella section, extending from 45 ky prior to the onset of the Olduvai magnetochron at 1.95 Ma to shortly before the end of it at 1.77 Ma. The Faella faunal assemblage will therefore play a key role in the geochronology of the UV faunal events, which occurred during the deposition of the Montevarchi intermediate fluvial-deltaic sequence, because the specimens occupy a wide range of ages and the lowermost ones represent the earliest fauna of the late Villafranchian, close to the beginning of the Mammal zone MN 17 of the Neogene classification.. Its magnetostratigraphic date, ranging from 1995 Ma to 1.775 Ma, represents the first example in the UV fossil collections of a measured time span within one assemblage collected in stratigraphic order. The biochronological position of the late Villafranchian reconstructed in the UV, and the present example will represent a criterion for dating most old collections, especially the classical ones, whenever a magnetostratigraphy of the units containing them will be available for correlation.